The Development of Scientific Cooperation under the Norway–Russia Fisheries Regime in the Barents Sea - Maria Hammer; Alf Håkon Hoel (Arctic Review on Law and Politics, 2012)
Cooperation between Norwegian and Russian scientists on marine science in the Barents Sea dates back to the 1950s. Science, as well as the resource management it serves, has evolved dramatically since then. In terms of its substance, scientific foci and methods have increased substantially. Previously, research efforts targeted a few commercial fish species, whereas entire ecosystems and non–commercial as well as commercial species are addressed today. A further dimension of change is that of organization of science: While cooperation was initially sporadic, it has gradually become embedded in a wider framework of scientific collaboration and become more organized. This framework is included in the bilateral management of the living marine resources in the Barents Sea. The Norwegian–Russian Joint Fisheries Commission (JNRFC) and the International Council for the Exploration of the Sea (ICES) work as the peer reviewers of science and providers of scientific advice to the authorities in Norway and the Russian Federation. This article discusses these issues with regard to developments in science, in international regimes and the role of science in policy-making.